Afghanistan, Neo-Taliban And the Possibility of Terrorism Escasion in Indonesia From a National Security Perspective - wibowo, ardianto bayu (UI Scholars Hub, 2023)
This study aims to analyze Neo-Taliban changes in controlling Afghanistan and interpret the perception of the Neo-Taliban victory that can trigger the rise of terror acts in Indonesia, as well as clarify the anticipation of the rise of terror acts over the euphoria of the Taliban victory in Afghanistan from a national security perspective. Ethnography is used as a method in this study to explore the phenomenon of terrorism which was inspired by the victory of the Taliban in Afghanistan. The results of the study show that Neo-Taliban changes that are considered rulers in Afghanistan are not due to an absolute victory but the Doha peace agreement. The perception of the Neo-Taliban victory can be euphoric, especially on the 20th anniversary of the 911 incident which is feared to encourage acts of terror. Anticipation that needs to be done is patrols on social media to reduce the euphoria of reporting the Taliban victory.